Effects of Segregated Early Weaning at 7 Days on Dams Body Condition, Parturition Interval and Offspring Birth Weight and Litter Size in the Agouti (Dasyprocta Leporina) for Intensive Production - Mohammed, Riyadh; Sant, Kavita Kemeela; Garcia, Gary Wayne (Animal Review, 2019)
There has been limited information reported on the impacts of segregated early weaning on agouti (Dasyprocta leporina) dams. The study lasted 485 days where 4 parturitions were recorded from 12 (2 year old) multiparous dams, hence there were 48 (12 x 4) parturitions in total with 100 offspring being born. Data was collected on 1) the live weight gain of dams (+/- g), 2) re-conception time and parturition interval (through theoretical calculations assuming that the gestation period was 104 days), 3) litter size at each parturition 4) weight of each individual offspring born per litter as a % of dams’ live weight and 5) the ratio of offspring sex at each parturition. Results showed that dams can reconceive and have a successive parturition as early as 119 days after the day of her previous parturition. Average live weight gain after 4 consecutive parturitions for dams were 276g. Average offspring weights increased by approximately 23 g (193 g to 216g) after 4 parturitions when weaned at 7 days. Average litter size per dam increased by 33% (1.75 to 2.33) after 4 parturitions when weaned at 7 days. Litter size as a percentage of dam’s body weight increased by 0.11% (5.47 to 5.58) after 4 parturitions when weaned at 7 days. This study concludes that weaning at 7 days post-partum is very beneficial for dams’ body condition and re conception, offspring growth and development and for continuous reproduction in an intensive production unit.